What is 9y 18?
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. And using ^ to indicate powers (eg x-squared = x^2).
1 person found this useful
9y - 18 = 3y subtract 3y from both sides 6y - 18 = 0 add 18 to both sides 6y = 18 divide by 6 on both sides y = 3
-9y=-18 Divide by negative 9 . y=2
The GCF is 9.
9y - 9 = -117 9y - 9 + 9 = -117 + 9 9y = -108 9y/9 = -108/9 y= -12
(y + 6)(y + 3)
If 92y = 36 then y = 36/92 = 9/23 So then 9y = 9*(9/23) = 81/23 or 3 12 / 23
y = 3 in the equation 31 = 4 - 9y Solve for y. 31 - 4 = 4 - 9y - 4 Simplify 27 = 9y Divide both sides by 9 to get the term y by itself on one side of the equation. 27 …/ 9 = 9y / 9 Simplify 3 = y
First, you want to get the y on one side of the equation and everything else on the other side. To do this, add 3x to each side: 9y = 3x + 18 The next step is to divide bo…th sides by 9, which gives you the equation solved for y: y = x/3 + 2
That is an equation, with an infinite number of solutions. It simplifies to y = 2/3 * x - 2. Two solutions are x = 6, y = 2, and x = 9, y = 4.
We have 3x+9y=36, or equivalently 12x+36y=144. We also have 12x+4y=18, so subtracting these we have 32y=126 or y=63/16. Substituting this into our original equation leaves 3x=…36-9*63/16 or x = 12-3*63/16 = 3/16. So: x=3/16, y=63/16
18x - 9y + 3z = 18 First, just to clean it up a bit, divide both sides of the equation by 3. (This doesn't change the equation or its graph in any way.) 6x - 3y + z = 6 A…t the 'x'-intercept , 'y' and 'z' are zero: 6x = 6 x = 1 At the 'y'-intercept , 'x' and 'z' are zero: -3y = 6 -y = 2 y = -2 At the 'z'-intercept , 'x' and 'y' are zero: z = 6
x - 9y = 18 At the x-intercept , y=0 : x = 18 At the y-intercept , x=0 : -9y = 18 -y = 2 y = -2
The x-intercept would be 4x + 9(0)= 18 so x = 4.5 (4.5,0) the y-intercept you'd make the x=0. 4(0) + 9y = 18 so y=2 (0,2)
4y + 10 = -18 4y = -28 y = -7
2X + 6Y = 12 3X + 9Y = 18 try elimination - 3(2X + 6Y = 12) 2(3X + 9Y = 18) - 6X - 18Y = - 36 6X + 18Y = 36 === I will say this system is dependent and an …infinite number of solutions can be found.
Assume the equation is 2x + 9y = 18. Then, there is no answer to this problem without the further details about the values for x or y! Include some information and objec…tive for the problem. Some details you might want to include are: . Find the slope of the equation. [Then, you need to solve for y and use the slope-intercept form y = mx + b!] . Find the solution, given another equation. . Graph the function.